State Defense Forces and Homeland Security - Tulak, Arthur N.; Kraft, Robert W.; Silbaugh, Don (2004)
As U.S. Northern Command (NORTHCOM) assumes responsibility within the Department of Defense for the homeland security and homeland defense missions, it does so with few assigned forces. While the "Forces For" apportionment to NORTHCOM is still being finalized, they will in any case be meager in comparison to the scope of the task and the assigned area of responsibility. The paucity of forces available to NORTHCOM will require more economical approaches to force-building for contingency operations in support of homeland security missions. While the National Guard is ideally positioned and suited for homeland security, it may not always be available in adequate numbers if called to active federal duty in support of military operations overseas. In addition to the forces the National Guard may provide, State Defense Forces -- military forces created, funded, and controlled solely by the individual states, and already integrated into the emergency management operations of more than 20 states -- are a potential force-provider for homeland security operations. Published in Parameters, U.S. Army War College Quarterly, v33 n4, p132-146, Winter 2003-2004.